2003
DOI: 10.1590/s1516-89132003000400022
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Pb and Cd in two impacted watersheds in Southeast Brazil, using the freshwater mussel Anodontites trapesialis (Lamarck, 1819) (Bivalvia : Mycetopodidae) as a biological monitor

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
(57 reference statements)
1
15
1
6
Order By: Relevance
“…Em estudos realizados com Anodontites trapesialis não foram encontradas correlações significativas entre peso corporal e concentração de metais. 28 Com relação às diferenças de concentrações de metais, outra correlação que não foi possível realizar com essa espécie foi com relação ao sexo, uma vez que pelas informações bibliográficas disponíveis (já que não se têm muitos dados sobre essa espécie) se acredita que a mesma é hermafrodita. A mesma tendência foi observada na Anodontites trapesialis.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em estudos realizados com Anodontites trapesialis não foram encontradas correlações significativas entre peso corporal e concentração de metais. 28 Com relação às diferenças de concentrações de metais, outra correlação que não foi possível realizar com essa espécie foi com relação ao sexo, uma vez que pelas informações bibliográficas disponíveis (já que não se têm muitos dados sobre essa espécie) se acredita que a mesma é hermafrodita. A mesma tendência foi observada na Anodontites trapesialis.…”
Section: Resultsunclassified
“…A mesma tendência foi observada na Anodontites trapesialis. 28 De maneira geral, as concentrações de Pb determinadas para a espécie Anodontites tenebricosus ultrapassaram os limites máximos de tolerância para contaminantes inorgânicos em peixes e produtos de pesca estabelecidos pela legislação brasileira para consumo humano (Portaria 658/98 da ANVISA, 29 equivalente a 2,0 µg/g para este metal), para todos os pontos de amostragem com exceção do ponto correspondente ao valor de background (CR-ANO), conforme observado na Figura 1.…”
Section: Resultsunclassified
“…El-Mex Bay area exhibited wide fluctuation in salinity affected by discharge of huge amounts of agricultural, sewage and industrial waste waters [24]. At S‰ was equal 30 ppm, clams may be releasing a protein due to the stress, they under that may cause cloudiness [25]. [25] stated that variation in the physiology of marine animal might have affected the intake of metals by the organisms and that the effectiveness of metal intake may differ in relation to ecological needs and metabolism of animals and concentrations of the heavy metals in water and food as well as other factors such as salinity and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…At S‰ was equal 30 ppm, clams may be releasing a protein due to the stress, they under that may cause cloudiness [25]. [25] stated that variation in the physiology of marine animal might have affected the intake of metals by the organisms and that the effectiveness of metal intake may differ in relation to ecological needs and metabolism of animals and concentrations of the heavy metals in water and food as well as other factors such as salinity and temperature. [26] and [27] reported that a single biomarker cannot provide the basic answers as to what is the actual state of health in the natural populations and that, environmental stress may cause changes in cellular function that alter the physiology of organ system in organisms, suggesting that pollutants might influence the metabolism of the whole organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation